Open MRI assessment of anterior femoroacetabular clearance in active and passive impingement-provoking postures. (28th November 2021) - Mohtajeb, Maryam; Cibere, Jolanda; Mony, Michelle; Zhang, Honglin; Sullivan, Emily; Hunt, Michael A.; Wilson, David R.
Abstract : Aims: Cam and pincer morphologies are potential precursors to hip osteoarthritis and important contributors to non-arthritic hip pain. However, only some hips with these pathomorphologies develop symptoms and joint degeneration, and it is not clear why. Anterior impingement between the femoral head-neck contour and acetabular rim in positions of hip flexion combined with rotation is a proposed pathomechanism in these hips, but this has not been studied in active postures. Our aim was to assess the anterior impingement pathomechanism in both active and passive postures with high hip flexion that are thought to provoke impingement. Methods: We recruited nine participants with cam and/or pincer morphologies and with pain, 13 participants with cam and/or pincer morphologies and without pain, and 11 controls from a population-based cohort. We scanned hips in active squatting and passive sitting flexion, adduction, and internal rotation using open MRI and quantified anterior femoroacetabular clearance using the β angle. Results: In squatting, we found significantly decreased anterior femoroacetabular clearance in painful hips with cam and/or pincer morphologies (mean -11.3° (SD 19.2°)) compared to pain-free hips with cam and/or pincer morphologies (mean 8.5° (SD 14.6°); p = 0.022) and controls (mean 18.6° (SD 8.5°); p < 0.001). In sitting flexion, adduction, and internal rotation, we found significantly decreased anterior clearance in both painful (mean -15.2° (SD 15.3°); p = 0.002) and painfree hips (mean -4.7° (SD 13°); p = 0.010) with cam and/pincer morphologies compared to the controls (mean 7.1° (SD 5.9°)). Conclusion: Our results support the anterior femoroacetabular impingement pathomechanism in hips with cam and/or pincer morphologies and highlight the effect of posture on this pathomechanism. Cite this article: Bone Jt Open 2021;2(11):988–996.